Simple and effective: T90 codends improve size selectivity and catch efficiency compared with diamond-mesh codends for mantis shrimp (Oratosquilla oratoria) in demersal trawl fishery of the South China Sea - Yang, Bingzhong; Herrmann, Bent (Frontiers in Marine Science, 2022)
Size selectivity and catch efficiency of four codends were tested and compared for mantis shrimp (Oratosquilla oratoria) in demersal trawl fisheries of the South China Sea (SCS). These codends were differing at mesh shapes, diamond-mesh (T0) and diamond-mesh turned 90 degree (T90), and mesh sizes, 30 and 35 mm, respectively. The results demonstrated that the T0 codend with lower mesh size, 30 mm, presented relatively poorer selective properties for the target species, while size selectivity would be significantly improved with the mesh size increasing to 35 mm, or substituting T0 codend with T90 codend. For T90 codend with larger mesh size, 35 mm, the size selectivity was the highest, whereas the loss of the legal individuals was also significantly considerable. Considering the trade-off between releasing undersized individuals and maintaining the legal ones, the T0 codend with 35 mm mesh size or the T90 codend with30 mm mesh size might be better choice to target mantis shrimp in demersal trawl fisheries of the SCS.